Vlog Worthy Surveillance?: Investigating the Playful Surveillance Imaginaries of South Korea’s Quarantine Vlogs - Lee, Jeehyun Jenny; Ahn, Chloe (Jae-Kyung) (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2024)
Through a case study of South Korean citizens’ YouTube quarantine vlogs, this study examines the cultural narratives and practices surrounding pandemic surveillance, mainly the government-mandated quarantine monitored via the quarantine mobile app. Moving beyond the dichotomous understanding of surveillance as an act of control either to be resisted or accepted, we draw on the framework of playful surveillance and surveillance imaginaries and examine how Korean citizens creatively vlog their experience in quarantine. Through a critical visual analysis of forty quarantine YouTube vlogs, we illustrate how Korean citizens build playful surveillance imaginaries, which are imaginaries about surveillance constructed through playful frames that perceive participation in surveillance as agentive, pleasurable, and relational. Their playful surveillance imaginaries introduce novel ways of perceiving the self, surveillance technologies, and others in surveillance cultures and the relations that bring them together into a mutually beneficial and caring network. However, the subversive potential of this empowering and relational mode of surveillance may be limited by Korean society’s normative understanding of care.